Ready or not - Stolz, Mary 1920- (New York Harper, 1953)
A sixteen-year-old girl, mother to a younger sister and brother, longs to be beautiful, and thus happy, until she meets a playground counselor who helps her see the importance of caring about the world and the realities of life.
Keywords: Family life -- Fiction; Domestic fiction